ANALYSIS OF INFLUENCING FACTORS AFFECTING AUDIT REPORT LAG - Miranda Setiyowati; Indira Januarti (Jurnal ASET (Akuntansi Riset), 2022)
The company's delay in reporting financial statements has increased yearly. This study aims to examine several variables that are considered to affect audit report lag. These factors include investment opportunities, profitability, company size, audit committee size, and auditor opinion. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2017-2019. The sampling method used was purposive sampling, using criteria for determining the sample so that 314 sample companies were obtained for three years of observation (2017 - 2019). The data analysis method used is multiple linear regression method. The results of this study indicate that profitability, size of the audit committee, and auditor opinion have a significant negative effect on audit report lag. In contrast, investment opportunity and company size have a negative and insignificant influence on audit report lag. This research provides an overview of good control and positive information from the company to be factors that can advance the submission of audited financial reports to policy-making authorities.